A sensitive OFF–ON–OFF fluorescent probe for the cascade sensing of Al3+ and F− ions in aqueous media and living cells. Issue 36 (5th June 2020) - Hou, Lingjie; Liang, Wenting; Deng, Chenhua; Zhang, Caifeng; Liu, Bo; Shuang, Shaomin; Wang, Yu
Abstract : A simple Schiff-base ligand 2-hydroxy-1-naphthaldehyde semicarbazone (HNS ) was synthesized and applied to the sequential sensing of Al 3+ and F − ions in aqueous media and live cells. Abstract : A simple Schiff-base ligand 2-hydroxy-1-naphthaldehyde semicarbazone (HNS ) was synthesized and characterized. Based on the combined effect of inhibition of CHN isomerization and chelation-enhanced fluorescence (CHEF), HNS functions as a fluorescence "turn on" sensor for Al 3+ in buffered aqueous media. Based on the strong affinity of Al 3+ to F − ions, the in situ generated Al 3+ –HNS complex can also be utilized as an effective chemosensor for F − sensing by metal displacement approach, ensuing quenching of fluorescence by the reversible return of HNS from Al 3+ –HNS complex. Thus a method using a single probe for the detection of both Al 3+ and F − ions is developed. The system exhibits high selectivity and sensitivity for Al 3+ and F − ions and the detection limits were found to be as low as 6.75 × 10 −8 M and 7.89 × 10 −7 M, respectively. Furthermore, the practical applicability of this probe has been examined in living cells.